Hubungan komunikasi interpersonal dengan kepuasan kerja pegawai di dinas pendidikan - Nellitawati Nellitawati; Yektri Yurmanita (Indonesian Institute for Counseling, Education and Therapy (IICET), 2019)
This study aims to see, 1) interpersonal communication in the Padang Education Authority, 2) job satisfaction in the Padang Education Authority, and 3) the relationship of interpersonal communication and job satisfaction of employees in the Padang Education Authority. The population of this study was 103 employees of the Padang City Education Office. The sample chosen was 53 employees determined based on proportional random sampling. Data collection is a questionnaire arranged in the form of a Likert scale. To test the relationship between two variables, we use the Product-moment correlation formula. The results showed that 1) job satisfaction in the Padang City Education Office was in the high category with a percentage of 73.93%. 2) Employee interpersonal communication in Padang City Education Office is in a good category with a percentage of 69.6%, and 3) there is a relationship between interpersonal communication and job satisfaction from gain of correlation tests with r count greater than r table at 2.575> 0.279 significant level 5% at 95% confidence level. Thus, it can be concluded that interpersonal communication has a meaningful relationship with job satisfaction in the Padang education authority. This means that the better the interpersonal communication, the higher the job satisfaction of employees in the Padang education authority and vice versa.